2004
DOI: 10.1152/ajprenal.00007.2003
|View full text |Cite
|
Sign up to set email alerts
|

Hexosamines and TGF-β1use similar signaling pathways to mediate matrix protein synthesis in mesangial cells

Abstract: Hyperglycemia-induced alterations in mesangial (MES) cell function and extracellular matrix (ECM) protein accumulation are seen in diabetic glomerulopathy. Transforming growth factor-beta1 (TGF-beta1) mediates high-glucose-induced matrix production in the kidney. Recent studies demonstrated that some of the effects of high glucose on cellular metabolism are mediated by the hexosamine biosynthesis pathway (HBP) in which fructose-6-phosphate is converted to glucosamine (GlcN) 6-phosphate. We previously showed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
2

Year Published

2005
2005
2009
2009

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 48 publications
0
21
2
Order By: Relevance
“…Hyperglycemia induces marked changes in mesangial cell function and ECM protein accumulation as seen in diabetic glomerulopathy (Isono et al, 2000;Singh et al, 2004). The hexosamine biosynthesis pathway is implicated in mediating several metabolic effects of high glucose and glutamine in cells.…”
Section: Protein Synthesis and Degradationmentioning
confidence: 99%
“…Hyperglycemia induces marked changes in mesangial cell function and ECM protein accumulation as seen in diabetic glomerulopathy (Isono et al, 2000;Singh et al, 2004). The hexosamine biosynthesis pathway is implicated in mediating several metabolic effects of high glucose and glutamine in cells.…”
Section: Protein Synthesis and Degradationmentioning
confidence: 99%
“…29 We have previously shown that high glucose, glucosamine and TGF-b1 increase PKC and PKA activities in renal mesangial cells and that downstream transcription factor CREB participates in fibronectin and laminin expression. [30][31][32] Nonetheless, the molecular basis for high glucose and hexossamineinduced cell-cycle arrest, mesangial ECM regulation and apoptosis are not fully understood.…”
Section: Introductionmentioning
confidence: 99%
“…For example, TGF-β induced apoptosis and Epithelial-to-Mesenchymal Transition (EMT) in AML-12 murine hepatocytes was associated with PKA activation [31] . Singh et al reported that laminin and fibronectin (Fn) expression induced by TGF-β1 could be down-regulated by PKA signaling blockage; however, the inhibition of PKC did not have significant effects on TGF-β1 [32] .…”
Section: Pparγ Agonists Suppressed Tgf-β1-induced Mcs Phenotype Altermentioning
confidence: 99%
“…After TGF-β combines with its receptor, the receptor phosphorylates PKA directly, with the formation of complexes between Smads and the regulatory subunits of PKA. Inhibition of the PKA signal pathway could block the matrix protein synthesis stimulated by TGF-β [9] .…”
Section: Introductionmentioning
confidence: 99%